The keratin 16 null phenotype is modestly impacted by genetic strain background in mice - Zieman, Abigail (Exp Dermatol, 2018)
The type I intermediate filament keratin 16 (K16) is constitutively expressed in ectoderm-derived appendages and is inducibly expressed in the epidermis upon barrier-compromising challenges. Dominantly acting missense alleles in KRT16 are causative for pachyonychia congenita (PC), a genodermatosis involving debilitating palmoplantar keratoderma (PPK), nail dystrophy, oral lesions and, frequently, alterations in glands and hair. C57Bl/6;Krt16(−/−) mice develop oral lesions early after birth and PC-like PPK lesions as young adults. These PPK lesions have a marked dysregulation of skin barrier-related genes and innate immunity effectors (eg danger-associated molecular patterns) and are preceded by oxidative stress secondary to hypoactive Nrf2 signalling. These molecular features are present in PPK lesions of PC patients. Here, we report that all components of the C57Bl/6;Krt16(−/−) mouse phenotype occur as well in the FVB strain background, albeit less severely so, a significant observation in the light of variations in the clinical presentation of individuals harbouring disease-causing mutations in the KRT16 gene.